EMPIRICAL SURVEY OF THE ALBANIAN JUDICIAL PRACTICE ON CRIMINAL OFFENSE OF “MANUFACTURING AND SALE OF NARCOTICS," PROVIDED BY ARTICLE 283 OF THE CRIMINAL CODE - Aleks Nikolli (European Scientific Journal, ESJ, 2014)
Purpose: This paper will examine theimplementationin practice by the Albanian courts of article 283 of the Criminal Code for the offense of "Production and sale of narcotics". Methodology: The study of case law is made by analyzing a random sample of 100 decisions of the courts of first instance. The survey sample is stratified, since 50 decisions were selected from Tirana District Court and the other 10 respectively decisions by district courts of Shkoder, Durres, Vlore, Korce and Elbasan. Findings: From the survey is found that 66% of cases declared guilty under article 283 of the Criminal Code are owned by drug keepers (58% for possession of cannabis and 8% for possessing hard drugs). Among other findings worth noting that most of the convicts were captured with small quantities of drugs and that 64% of cases the defendants were sentenced to the minimum that the law provides by imprisonment of 5 years. Conclusion: Article 283 of the Penal Code is not focused on punishing the criminals who promote the consumption of narcotics, but to the users of narcotics. Most of the convicts under this article were seized small amounts of drugs which mostly is cannabis. Imprisonment terms are not affected by the kinds of narcotic substance seized (cannabis or hard drugs) or by the quantity of that (small or huge quantities), but at the other hand the Albanian courts have taken full advantage of legal opportunities by allocating defendants the minimum provided by this article.